Chronic intraocular pressure elevation impairs autoregulatory capacity in streptozotocin‐induced diabetic rat retina. (20th December 2014) - Wong, Vickie H.; Armitage, James A; He, Zheng; Hui, Flora; Vingrys, Algis J.; Bui, Bang V.
Abstract Purpose To assess ocular blood flow responses to acute IOP stress following 4 weeks of chronic IOP elevation in streptozotocin (STZ)‐induced diabetic and control rats. We hypothesise that chronic IOP elevation for 4 weeks will further impair blood flow regulation in STZ‐induced diabetic rats eyes. Methods Two weeks following citrate buffer or STZ‐injections chronic IOP elevation was induced in Long Evans rats via fortnightly intracameral injections of microspheres (15 μm) suspended in 5% polyethylene glycol. IOP was monitored daily. Electroretinography (ERG, −6.79–2.07 log cd s m−2) was undertaken at Week 4 to compare photoreceptor (RmPIII), ON‐bipolar cell (Vmax) and ganglion cell dominant ERG [scotopic threshold response (STR)] components. 4 weeks post‐chronic IOP induction, ocular blood flow (laser Doppler flowmetry) was measured in response to acute IOP challenge (10–100 mmHg, in 5 mmHg steps, each 3 min). Results Four weeks of chronic IOP (mean ± S.E.M., citrate: 24.0 ± 0.3 to 30.7 ± 1.3 and STZ‐diabetes: 24.2 ± 0.2 to 31.1 ± 1.2 mmHg) was associated with reduced photoreceptor amplitude in both groups (−25.3 ± 2.2% and −17.2 ± 3.0%, respectively). STZ‐diabetic eyes showed reduced photoreceptor sensitivity (citrate: 0.5 ± 1.8%, STZ‐diabetic: −8.1 ± 2.4%). Paradoxically ON‐bipolar cell sensitivity was increased, particularly in citrate control eyes (citrate: 166.8 ± 25.9%, STZ‐diabetic: 64.8 ± 18.7%). The ganglion cell dominant STR was not significantly reduced in STZ‐diabetic rats. Using acute IOP elevation to probe autoregulation, we show that STZ‐diabetes impaired autoregulation compared with citrate control animals. The combination of STZ‐diabetes and chronic IOP elevation further impaired autoregulation. Conclusions STZ‐diabetes and chronic IOP elevation appear to be additive risk factors for impairment of ocular blood flow autoregulation.